2015
DOI: 10.1590/1809-4430-eng.agric.v35n5p918-930/2015
|View full text |Cite
|
Sign up to set email alerts
|

Mineralização do resíduo da pupunheira em condições de campo e laboratório

Abstract: RESUMO:Objetivou-se, neste trabalho, estudar o processo de decomposição do carbono (CO) e nitrogênio orgânico (NO) dos resíduos da pupunheira, em condições de campo e laboratório, e em duas formas de aplicação: com incorporação ou em disposição superficial no solo. O experimento de campo foi conduzido em Cambissolo Háplico Tb distrófico latossólico (CXbd), nas condições climáticas tropicais do período de primavera/verão, na cidade de Viçosa-MG, Brasil. Os resíduos foram incubados em condição de campo e laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
(8 reference statements)
1
11
0
3
Order By: Relevance
“…5b). This fact was also verified by Pereira et al (2015) and Paula et al (2013), when studying the mineralization of several residues in the soil. Paula et al (2013) concluded that the levels of inorganic nitrogen and, consequently, of organic nitrogen, are subject to the OCeo-easily oxidized organic carbon; TOC-total organic carbon; TN-otal nitrogen; MN-mineral nitrogen; ON-organic nitrogen; MfOCeo-mineralized fraction of organic carbon; MfON-mineralized fraction of organic nitrogen strong influence of climatic variations and, for this reason, have generated unreliable estimates of the mineralized fraction of the organic residues studied, as occurred in the present study.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…5b). This fact was also verified by Pereira et al (2015) and Paula et al (2013), when studying the mineralization of several residues in the soil. Paula et al (2013) concluded that the levels of inorganic nitrogen and, consequently, of organic nitrogen, are subject to the OCeo-easily oxidized organic carbon; TOC-total organic carbon; TN-otal nitrogen; MN-mineral nitrogen; ON-organic nitrogen; MfOCeo-mineralized fraction of organic carbon; MfON-mineralized fraction of organic nitrogen strong influence of climatic variations and, for this reason, have generated unreliable estimates of the mineralized fraction of the organic residues studied, as occurred in the present study.…”
Section: Resultssupporting
confidence: 59%
“…Comparing these results with those obtained by other authors, although they used other organic residues, it is verified that the organic carbon mineralization process in the present work was slower. When studying the decomposition process of organic carbon and organic nitrogen in peach-palm residues applied superficially to the soil or incorporated, at field and laboratory conditions, Pereira et al (2015), verified that the estimated mineralized fraction of OCeo was 50.98% after 28 days of incubation of the residue when it was applied on soil surface. Paula et al (2013), when analyzing different methods of estimating the mineralized fractions of cattle, pig and poultry manure, as well as sewage sludge and urban waste compost, incorporated or disposed superficially on a Dystrophic Red-Yellow Latosol (LVAd), verified that the estimated OCeo mineralized fractions were, after 30 days of incubation of the residue, higher than 75.6%, in the superficially disposed residues.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…A menor relação C/N no SC (18,6) e nos substratos provenientes da compostagem (RRU e LPF) provavelmente contribuiu para o maior crescimento das mudas de E. dunnii devido à maior disponibilidade de nitrogênio proveniente da mineralização da fração orgânica que, segundo Pereira (2013), apresenta relação inversa entre a relação C/N e a disponibilidade de nitrogênio no substrato. Nos substratos com elevada relação C/N (RLD e DLB), provavelmente a baixa disponibilidade de nitrogênio devido à imobilização do nutriente pelos microrganismos no processo de decomposição dos resíduos orgânicos tenha sido o fator que afetou o crescimento das mudas de E. dunnii (Andreani et al, 2011).…”
Section: Espécies Substratosunclassified